Impact of the fear of catching COVID-19 on anxiety, depression, and insomnia in undergraduate students - Chávez Cerna, Blanca Victoria (2020)
The objective of the study was to evaluate the impact of the fear of catching COVID-19 on the level of anxiety, depression, and insomnia in 1002 university students of both sexes (41.4% males and 58.6% females) between the ages of 17 and 35 (M=21.4; SD=3.4). The Fear of catching COVID-19 Scale, the Generalized Anxiety Disorder Scale (GAD-7), the Patient Health Questionnaire (PHQ-9) and the Insomnia Severity Index (ISI) were used to measure the variables. The results of the study show that the concern about getting COVID-19 significantly influences the level of anxiety (β = 52; p<,01), insomnia (β =.44; p <.01) experienced by university students (χ2 = 2210.39; df = 371; p = .000; RMSEA = .070 [IC90% .068 – .073]; SRMR = .053; CFI = .95; TLI = .94). The descriptive results show that a notable percentage of university students present significant symptoms of anxiety (22.7%), depression (23.7%) and insomnia (33%). It is concluded that the concern about getting COVID-19 is a serious health problem since it influences the appearance of anxiety, depression and insomnia symptoms.